Pengaruh Kredibilitas Selebriti Endorser Nasional VS Internasional Pada Niat Beli Luwak Whte Koffie - Saragih, Novia Moliana; Junaedi, MF. Shellyana (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2017)
The reseach of this study to analysing of credibility effect (attractiveness, trusworthiness and expertise) and different analysing national endorser nor international endorser to consumer purchase intention. This reseach using the student respondent of several university in Yogyakarta city. The valid sample are 277 respondent. The result of study using multiple linear regression showed that trusworthiness expertise of national endorser celebrity significant effect on consumer purchase intention on Luwak White Koffie product. But attractiveness of celebrity national endoser no significant effect on consumer purchase intention on Luwak White Koffie product. The result used independent sample t-test showed national endoser celebrity more trusworthy and more capable advertised product compare with international endoser celebrity. It is just, international endoser celebrity attractiveness more of consumer compare national endoser celebrity. Keyword: Celebrity Endorser, Endorsement, Endorser Celebrity Attractiveness, Endorser Celebrity Attractiveness, Endorser Celebrity Expertise